Educated Youth Entrepreneurs: Possibly the Answer to Our Economic Problems? - Ika Suhartanti Darmo (Universitas Pahlawan Tuanku Tambusai, 2022)
Thirty percent of Bina Nusantara University's alums are young business owners, according to the university's monitoring findings. The methodology employed is a survey study, with data collected from a representative sample of 214 graduates (n=69) via online surveys and evaluated using descriptive statistics in the outset of 2022. Educated young entrepreneurs' averaged performance was pretty good, showing a 3.11 on a 4.0 scale. The business owner's passion, mental preparedness to handle competition, and communication skills in developing relationships with business partners are all fairly strong, judging from the indicator's average score above. The company's history and the government's assistance are to blame for its below-average worth. This demonstrates that the company is still in its early stages of development and that performance is still poor, both of which are linked to the absence of governmental backing. A lack of business capital, a decline in people's economic conditions that weakens consumer purchasing power, a lack of business skills on the part of young entrepreneurs, high levels of intense business competition, and fluctuations in product/service quality marketed to the public were all cited as factors limiting the performance of educated young entrepreneurs.